PENGARUH LINGKUNGAN KERJA, KEPEMIMPINAN, DAN MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI DINAS PERTANIAN TANAMAN PANGAN DAN HOLTIKULTURA PROVINSI JAWA TENGAH - Noor Nasichah, 10.05.51.0109 (Students Journal of Economic and Management, 2013)
The study aims to examine and analyze the influence of work environmenton, leader ship and motivation to the work performance employee of department of agriculture and horticulture crops province of Central Java. Based on the calculation formula slovin samples in this study amounted to 54.5 roundedto 90 respondents. These research ersuse a method Random Sampling. Using quantitative and qualitative analysis that includes the Test Validity, Test Profitability, Multiple linier Regressi on and Coefficient of Determination. Techniques of data analysis in this study using multiple linear regression while hypothesis testing using test and F test Based on survey results revealed that there are positive and significant influence between work environment (X1) on the work performance (Y), there isa significant and positive effect between leader ship (X2) on the work performance (Y), there are positive and not significant between motivation (X3) on work performance (Y), motivation, discipline and work environment work together have a positive and significant impact on employee performance. Based on the coefficient of determination there is the influence of motivational variables (X1), the variable of work discipline (X2), the work environment variables (X3) jointly affect the performance variable (Y) is 61,2% Keywords, Work Environment leader ship, motivation, work Performance.